Preparation of Silver-Chitosan Nanocomposites Colloidal and Film as Antibacteri Material - Endang Susilowati; Mohammad Masykuri; Maria Ulfa; Dyah Puspitasari (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2020)
Colloidal nanocomposites silver-chitosan have been made. Silver nanoparticles were produced by chemical reduction methods assisted microwave irradiation using chitosan from crab shells as a reducing agent and stabilizer, AgNO3 as a precursor and NaOH as an accelerator. This study investigated AgNO3 concentration toward localized surface plasmon resonance (LSPR) phenomenon of nanocomposites colloidal. The size and shape of the silver nanoparticles were confirmed by TEM. Furthermore, the stability of the storage was observed for twelve weeks. Colloidal and film nanocomposites silver- chitosan have been made by casting method by drying at room temperature. After that, the film characterization was carried out, including swelling with gravimetry methods and surface morphology using scanning electron microscopy (SEM). Diffusion methods tested colloid antibacterial activity and silver-chitosan nanocomposite film’s against E. Coli and S. Aureus. The results showed that the formation of silver nanoparticles was identified by the LSPR absorption band's appearance at 413-419 nm. The increasing of AgNO3 concentration increased the intensity of the LSPR absorption band. Silver nanoparticles with sizes of about 3-9 nm are spherical. The silver nanoparticles were stable at 12 weeks of storage. The higher AgNO3 concentration tends to increase the swelling of the film. The surface of the silver-chitosan nanocomposite film’s was rougher than that of the chitosan film. The higher the silver nanoparticle concentration, the higher the colloid and film antibacterial activity against E. Coli and S. Aureus.